Determination of Sliced Pineapple Drying Characteristics in A Closed Loop Heat Pump Assisted Drying System - Tunçkal, Cüneyt; Coşkun, Salih; Doymaz, İbrahim; Ergun, Ernes (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
Pineapple (Ananascomosus) slices were dried with the aid of a heat pump assisted dryer (HPD). During this process, air velocity was kept constant at 1m/s, while air temperatures were changed as 37°C, 40°C and 43°C. The drying air was also circulated by using an axial fan in a closed cycle and fresh air was not allowed into the system. The drying rate and drying time were significantly influenced by drying temperature. It was observed that drying temperatures had significant effects on the drying rate and drying time. During the conduct of the study, pineapple slices were dried at 37, 40 and 43°C for 465, 360 and 290 min, respectively. The specific moisture extraction ratio (SMER) values were observed to change as drying temperatures were changed. The drying rate curves indicated that the whole drying process occurred in the falling rate period. Seven well-known thin-layer models (Lewis, Henderson &Pabis, Logarithmic, Page, Midilli & Kucuk, Weibull and Aghbashlo et al.) were employed to make a prediction about drying kinetics through nonlinear regression analysis. The Midilli & Kucuk and Aghbashlo et al. models were consistent with the experimental data. Fick’s second law of diffusion was used to determine the moisture diffusivity coefficient ranging from 3.78×10–9 to 6.57×10-9 m2/s the each of the above mentioned temperatures. The dependence of effective diffusivity coefficient on temperature was defined by means a fan Arrhenius type equation. The activation energy of moisture diffusion was found to be 75.24kJ/mol. Article History: Received: July 18th 2017; Received: October 27th 2017; Accepted: January 16th 2018; Available onlineHow to Cite This Article: Tunçkal, C., Coşkun, S., Doymaz, I. and Ergun, E. (2018) Determination of Sliced Pineapple Drying Characteristics in A Closed Loop Heat Pump Assisted Drying System. International Journal of Renewable Energy Development, 7(1), 35-41.https://doi.org/10.14710/ijred.7.1.35-41